Urbanisation at risk in the Pacific and Asia disasters, climate change and resilience in the built environment - Sanderson, David (Routledge, 2020)
"This book presents practical approaches for tackling the threats from climate change and disasters to urban growth in Pacific island countries and Asian nations. With chapters written by leading scholars and practitioners, Urbanisation at risk presents research and case studies from island countries across the Pacific, Cambodia, Nepal, and the Philippines. The book explores and presents the theory, policy, and practice of how governments, civil society, aid organisations, and people themselves prepare for, withstand and recover better from urban disasters including windstorms, floods, earthquakes and fires, and the effects of climate change. This book is written for urban policy makers, researchers, humanitarian aid and development workers, and anyone interested in urbanisation, participatory approaches, disasters, resilience, and climate change adaptation"--